1
$\begingroup$

I'm doing an exercise in which I need to show that the DCT of $\tilde{x} = (x_{N-1}, x_{N-2}, ..., x_1, x_0) $, with $\tilde x_m = x_{N-m-1}$, is equal to $ \tilde{X}_k = (-1)^{k}X_{k}$, but I have difficulty with the indices in the cosine manipulation and $\tilde x$:

\begin{eqnarray*} \tilde X_k &=& \sqrt{\frac{2}{N}}\sum_{m=0}^{N-1}\tilde x_{m}\cos\bigg(\frac{\pi k(N-m-1+\frac{1}{2})}{N}\bigg) \\ &=& \sqrt{\frac{2}{N}}\sum_{m=0}^{N-1}\tilde x_{m} \cos\bigg(\frac{\pi k(N-m-\frac{1}{2})}{N}\bigg) \\ &=& \sqrt{\frac{2}{N}}\sum_{m=0}^{N-1}\tilde x_m \cos\bigg(\frac{\pi k(-m-\frac{1}{2})}{N} + \pi k \bigg) \\ &=&\sqrt{\frac{2}{N}}\sum_{m=0}^{N-1}\tilde x_m \cos\bigg(\pi k - \frac{\pi k(m + \frac{1}{2})}{N} \bigg) \\ &=&\sqrt{\frac{2}{N}}\sum_{m=0}^{N-1} x_m (-1)^{k}\cos\bigg(\frac{\pi k(m + \frac{1}{2})}{N} \bigg) \\ &=&(-1)^{k}\sqrt{\frac{2}{N}}\sum_{m=0}^{N-1} x_m \cos\bigg(\frac{\pi k(m + \frac{1}{2})}{N} \bigg) \\ &=& (-1)^k X_k \end{eqnarray*}

$\endgroup$
2
  • 1
    $\begingroup$ Isn't a tilde missing in $x_k = x_{N-k-1}$? $\endgroup$ Commented May 17, 2020 at 20:15
  • $\begingroup$ I have tried to simplified some notations, hoping this is correct $\endgroup$ Commented May 17, 2020 at 20:39

0

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Browse other questions tagged or ask your own question.